Analisis Rata-Rata Lama Sekolah, Angka Partisipasi Kasar Sekolah Menengah Atas dan Upah Minimum Provinsi Terhadap Tingkat Pengangguran Terbuka di Provinsi Maluku - Wicky Aulele; Yerimias Manuhutu; Izaac Tonny Matitaputty; Sondang Siahaan (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This research is motivated by the problem of the open unemployment rate in Maluku Province which is still fluctuating, where the influence of human capital indicators such as the Average Years of Schooling and the Gross Enrollment Rate of Senior High Schools as well as economic policies such as the Provincial Minimum Wage often show results inconsistent with theory, thus requiring further empirical studies to determine their influence in the region. The purpose of this study is to analyze and determine the partial and simultaneous effects of the average years of schooling, the gross enrollment rate of senior high schools, and the provincial minimum wage on the open unemployment rate in Maluku Province. The method used is quantitative with secondary data in the form of time series from 2015 to 2024 sourced from the Central Statistics Agency (BPS) of Maluku Province, and analyzed using multiple linear regression techniques. The results show that the average years of schooling have a negative and significant effect, while the gross enrollment rate of senior high schools and the provincial minimum wage each have a positive insignificant and negative insignificant effect on the open unemployment rate. Simultaneously, the three variables also have no significant effect. The implications of these findings confirm that increasing the average length of schooling is a key factor in reducing unemployment, but policies related to minimum wages and high school participation need to be reviewed and combined with other policies to be more effective in addressing unemployment in Maluku Province.